Prioritizing Shark, Ray, and Chimaera Conservation in Rapidly Changing Polar Waters - Vanessa B. Bettcher; Amanda Batlle‐Morera; Peter M. Kyne; Ryan Charles; Emiliano García‐Rodríguez; Christoph A. Rohner; Asia O. Armstrong; Margaret O’Leary Amsler; Natalia V. Chernova; Brynn M. Devine; Andrey V. Dolgov; Meghan M. Donovan; et al. (Global Change Biology, 2026)
Climate‐driven alterations in sea‐ice dynamics and shifting fishing activity are reshaping ecosystems across the Arctic and Antarctic, yet conservation‐relevant information for chondrichthyans (sharks, rays, and chimaeras) remains limited. We present the first assessment of Important Shark and Ray Areas (ISRAs) across Polar Waters, integrating species distributions, extinction risk, critical habitat evidence, spatial protection coverage, apparent fishing effort (2013–2018 vs. 2019–2024), and sea‐ice concentration trends. Of 86 chondrichthyan species reported from Polar Waters, only 15 (17.4%) had sufficient evidence to meet the ISRA Criteria, and 28 (32.6%) are threatened with extinction. We identified 35 ISRAs (27 Arctic; 8 Antarctic) covering 0.75% of the Polar Waters region. ISRAs were delineated predominantly based on data from scientific fishing surveys and harvest fisheries. Most Antarctic ISRAs were delineated under Criterion B—Range Restricted, reflecting endemism and scarce life‐history evidence. Major knowledge gaps persist, particularly for highly adapted Polar Species (10 species) and deepwater taxa (72.1% of regional chondrichthyan fauna). Between 2013 and 2024, the spatial footprint of fishing expanded in both poles for trawlers and longliners, despite stable or declining fishing hours in some fleets. Concurrent areas of increasing fishing effort and decreasing sea‐ice concentration remained minimal. However, apparent fishing effort overlapped with most ISRAs, indicating ongoing fishing pressure in critical habitats. Marine Protected Area (MPA) coverage remains uneven: 8.2% of Arctic ISRA spatial extent overlaps MPAs (0.8% no‐take), compared with 43.8% in the Antarctic (14.8% no‐take), with insufficient effective coverage in areas beyond national jurisdiction. These results reveal substantial mismatches between chondrichthyan critical habitats, fishing exposure, and existing protection measures. Integrating ISRAs into existing management frameworks, such as Target 3 of the Global Biodiversity Framework, High Seas Treaty mechanisms, and fisheries governance bodies, will be essential to safeguard vulnerable polar chondrichthyans as sea‐ice concentration declines and exposure risk increases.

A VNIR spectral database of terrestrial magmatic rocks for the interpretation of Martian plagioclase hyperspectral detections - M. Barthez; J. Flahaut; M. Guitreau; R. Pik; G. Ito; C. Delangle; J.-P. Gremilliet; B. Luais; F. Faure (Icarus, 2026)

A reappraisal of the amorphization kinetics of water ice: Combined experimental and numerical investigations and amorphization cross-sections in the 90–120 K range - A. Moingeon; E. Quirico; O. Poch; M. Faure; P. Boduch; A. Domaracka; H. Rothard; B. Schmitt; M. Toulemonde; J. Rangama; D. Bockelée-Morvan; T. Fouchet; et al. (Icarus, 2026)

Toxicity of polycaprolactone nanoplastics, pristine or weathered in environmental conditions, to human intestinal epithelial cells, in vitro - M. Boulée; V. Bard; M. Papin; D. Béal; S. Devineau; D. Fenel; E. Dusacq; V. Collin-Faure; T. Rabilloud; T. Douki; M. Carriere (NanoImpact, 2026)

Characteristics and modelling of slip-rate variability and temporal earthquake clustering across a distributed network of active normal faults constrained by in situ 36Cl cosmogenic dating of fault scarp exhumation, central Italy - G.P. Roberts; F. Iezzi; C. Sgambato; J. Robertson; J. Beck; Z.K. Mildon; I. Papanikolaou; A.M. Michetti; J.P. Faure Walker; S. Mitchell; M. Meschis; R. Shanks; et al. (Journal of Structural Geology, 2025)

Transition from a fixed fee to a pay-as-you-throw waste tariff scheme: Effectiveness of environmental and accountability appeals - Lesman Ghazaryan; Corinne Faure; Joachim Schleich; Mia M. Birau (Journal of Environmental Management, 2025)

Complete genome sequences of three Prunus-infecting nepoviruses: apricot latent ringspot virus, myrobalan latent ringspot virus, and a novel virus from smooth stone peach (Prunus mira Koehne) - M. Khalili; T. Candresse; C. Faure; Y. Brans; A. Marais (Archives of Virology, 2024)

Spatial migration of temporal earthquake clusters driven by the transfer of differential stress between neighbouring fault/shear-zone structures - G.P. Roberts; C. Sgambato; Z.K. Mildon; F. Iezzi; J. Beck; J. Robertson; I. Papanikolaou; A.M. Michetti; J.P. Faure Walker; M. Meschis; R. Shanks; R. Phillips; et al. (Journal of Structural Geology, 2024)

Absence of low-δ18O magmas despite widespread assimilation of altered crust in a large magmatic and hydrothermal province - Shane M. Rooyakkers; Isabelle Chambefort; Kevin Faure; Colin J.N. Wilson; Simon J. Barker; Nick Mortimer; Hannah C. Elms; Juliana Troch; Bruce L.A. Charlier; Graham S. Leonard; David Farsky (Geochimica et Cosmochimica Acta, 2023)

A ring trial to harmonize Toxoplasma gondii microsatellite typing: comparative analysis of results and recommendations for optimization - M. Joeres; G. Cardron; K. Passebosc-Faure; N. Plault; M. Fernández-Escobar; C. M. Hamilton; L. O’Brien-Anderson; R. Calero-Bernal; L. Galal; C. Luttermann; P. Maksimov; F. J. Conraths; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)
A ring trial among five European laboratories was organized to reach consistency in microsatellite (MS) typing of the zoonotic parasite Toxoplasma gondii . Three sample sets were circulated and analyzed by each laboratory following a previously published method that is based on fragment length polymorphism of 15 MS markers. The first sample set compared typing results in general and focused on effects of DNA concentration; the second sample set focused on the polymorphic fingerprinting markers that can differentiate T. gondii strains within the same archetypal lineage; and the third set focused on non-archetypal genotypes. Methodological variations between laboratories, including the software programs used to determine MS fragment length, were collated using a questionnaire. Overall, lineage-level typing results reached a high level of agreement, especially in samples with the highest DNA concentrations. However, laboratory-specific differences were observed for particular markers. Major median differences in fragment length, of up to 6 base pairs, were related to the fluorophore used to label fragment-specific primers. In addition, primer pairs with identical sequences obtained from different suppliers resulted in fragments of differing length. Furthermore, differences in the way the sequencing profiles were assessed and interpreted may have led to deviating results in fragment length determination. Harmonization of MS typing, for example, by using the same fluorophores or by numerical adjustments applied to the fragment-lengths determined, could improve the uniformity of the results across laboratories. This is the first interlaboratory comparison, providing guidelines (added as a supplement) for the optimization of this technique.

Non-destructive methods to assess pesticide exposure in free-living bats - Natalia Sandoval-Herrera; Jesusa Paz Castillo; Ma. Enrica Angela Ching; L. Gerardo Herrera M.; Paul A. Faure; Kenneth Welch (Science of The Total Environment, 2023)

On a radiolytic origin of red organics at the surface of the Arrokoth Trans-Neptunian Object - Eric Quirico; Aurore Bacmann; Cédric Wolters; Basile Augé; Laurène Flandinet; Thibault Launois; John F. Cooper; Véronique Vuitton; Thomas Gautier; Lora Jovanovic; Philippe Boduch; Hermann Rothard; et al. (Icarus, 2023)

Interpreting biomonitoring data: Introducing the international human biomonitoring (i-HBM) working group's health-based guidance value (HB2GV) dashboard - Shoji F. Nakayama; Annie St-Amand; Tyler Pollock; Petra Apel; Yu Ait Bamai; Dana Boyd Barr; Jos Bessems; Antonia M. Calafat; Argelia Castaño; Adrian Covaci; Radu Corneliu Duca; Sarah Faure; et al. (International Journal of Hygiene and Environmental Health, 2023)

Identification of two novel putative satellite RNAs with hammerhead structures in the virome of French and Spanish carrot samples - B. M. Babalola; D. Schönegger; C. Faure; A. Marais; A. Fraile; F. Garcia-Arenal; T. Candresse (Archives of Virology, 2022)

Complete genome sequence of cherry virus T, a novel cherry-infecting tepovirus - A. Marais; D. Šafářová; M. Navrátil; C. Faure; D. Cornaggia; Y. Brans; J. Suchá; T. Candresse (Archives of Virology, 2020)

Complete genome sequence of a novel grapevine-infecting member of the genus Polerovirus, grapevine polerovirus 1 - T. Candresse; A. Marais; C. Faure; M. Lefebvre; T. Lacombe; J. M. Boursiquot (Archives of Virology, 2020)

Status of potato viruses in Tunisia and molecular characterization of Tunisian Potato Virus X (PVX) isolates - Ahmed Ben Hafsa; Nesrine Nabi; Besma M’rabet Saamali; Mohammed Salem Zellama; Sébastien Theil; Chantal Faure; Aurélie Berard; Dominique Brunel; Marie-Christine Le Paslier; Armelle Marais; Thierry Candresse; Maher Chaouachi (European Journal of Plant Pathology, 2018)

Alterations in alpha5* nicotinic acetylcholine receptors result in midbrain- and hippocampus-dependent behavioural and neural impairments - Morgane Besson; Stefania Guiducci; Sylvie Granon; Jean-Philippe Guilloux; Bruno Guiard; Christelle Repérant; Philippe Faure; Stéphanie Pons; Giuseppe Cannazza; Michele Zoli; Alain M. Gardier; Uwe Maskos (Psychopharmacology, 2016)

Superficial Fungal Infections in a French Teaching Hospital in Grenoble Area: Retrospective Study on 5470 Samples from 2001 to 2011 - O. Faure-Cognet; H. Fricker-Hidalgo; H. Pelloux; M. T. Leccia (Mycopathologia, 2016)

Effect of thermal pre-treatment on the availability of PAHs for successive chemical oxidation in contaminated soils - M. Usman; A. Chaudhary; C. Biache; P. Faure; K. Hanna (Environmental Science and Pollution Research, 2016)

Diguanylate cyclase D gc P is involved in plant and human P seudomonas spp. infections - Isabel M. Aragon; Daniel Pérez‐Mendoza; Joana A. Moscoso; Emmanuel Faure; Benoit Guery; María‐Trinidad Gallegos; Alain Filloux; Cayo Ramos (Environmental Microbiology, 2015)
Summary The second messenger cyclic di‐ GMP (c‐di‐ GMP ) controls the transition between different lifestyles in bacterial pathogens. Here, we report the identification of D gc P (diguanylate cyclase conserved in P seudomonads), whose activity in the olive tree pathogen P seudomonas savastanoi pv. savastanoi is dependent on the integrity of its GGDEF domain. Furthermore, deletion of the dgc P gene revealed that D gc P negatively regulates motility and positively controls biofilm formation in both the olive tree pathogen P . savastanoi pv. savastanoi and the human opportunistic pathogen P seudomonas aeruginosa . Overexpression of the dgc P gene in P . aeruginosa PAK led to increased exopolysaccharide production and upregulation of the type VI secretion system; in turn, it repressed the type III secretion system, which is a hallmark of chronic infections and persistence for P . aeruginosa . Deletion of the dgc P gene in P . savastanoi pv. savastanoi NCPPB 3335 and P . aeruginosa PAK reduced their virulence in olive plants and in a mouse acute lung injury model respectively. Our results show that diguanylate cyclase D gc P is a conserved P seudomonas protein with a role in virulence, and confirm the existence of common c‐di‐ GMP signalling pathways that are capable of regulating plant and human P seudomonas spp. infections.

Effect of organic amendments on the mobility of trace elements in phytoremediated techno-soils: role of the humic substances - N. Hattab; M. Soubrand; R. Guégan; M. Motelica-Heino; X. Bourrat; O. Faure; J. L. Bouchardon (Environmental Science and Pollution Research, 2014)

Phylogeography in continuous space: coupling species distribution models and circuit theory to assess the effect of contiguous migration at different climatic periods on genetic differentiation in B usseola fusca ( L epidoptera: N octuidae) - S. Dupas; B. le Ru; A. Branca; N. Faure; G. Gigot; P. Campagne; M. Sezonlin; R. Ndemah; G. Ong'amo; P.‐A. Calatayud; J.‐F. Silvain (Molecular Ecology, 2014)
Current population genetic models fail to cope with genetic differentiation for species with large, contiguous and heterogeneous distribution. We show that in such a case, genetic differentiation can be predicted at equilibrium by circuit theory, where conductance corresponds to abundance in species distribution models ( SDM s). Circuit‐ SDM approach was used for the phylogeographic study of the lepidopteran cereal stemborer B usseola fusca F üller ( N octuidae) across sub‐ S aharan A frica. Species abundance was surveyed across its distribution range. SDM s were optimized and selected by cross‐validation. Relationship between observed matrices of genetic differentiation between individuals, and between matrices of resistance distance was assessed through Mantel tests and redundancy discriminant analyses ( RDA s). A total of 628 individuals from 130 localities in 17 countries were genotyped at seven microsatellite loci. Six population clusters were found based on a B ayesian analysis. The eastern margin of D ahomey gap between E ast and W est A frica was the main factor of genetic differentiation. The SDM projections at present, last interglacial and last glacial maximum periods were used for the estimation of circuit resistance between locations of genotyped individuals. For all periods of time, when using either all individuals or only E ast A frican individuals, partial M antel r and RDA conditioning on geographic distance were found significant. Under future projections (year 2080), partial r and RDA significance were different. From this study, it is concluded that analytical solutions provided by circuit theory are useful for the evolutionary management of populations and for phylogeographic analysis when coalescence times are not accessible by approximate B ayesian simulations.

Characterization of Erwinia amylovora strains from Middle Atlas Mountains in Morocco by PCR based on tandem repeat sequences - Najat Hannou; Pablo Llop; Denis Faure; María M. López; Mohieddine Moumni (European Journal of Plant Pathology, 2013)

Treatment of hydrocarbon contamination under flow through conditions by using magnetite catalyzed chemical oxidation - M. Usman; P. Faure; C. Lorgeoux; C. Ruby; K. Hanna (Environmental Science and Pollution Research, 2013)

Origin of the Matauri Bay halloysite deposit, Northland, New Zealand - R. L. Brathwaite; A. B. Christie; K. Faure; M. G. Townsend; S. Terlesk (Mineralium Deposita, 2012)

Genome-wide association analysis to identify chromosomal regions determining components of earliness in wheat - J. Le Gouis; J. Bordes; C. Ravel; E. Heumez; S. Faure; S. Praud; N. Galic; C. Remoué; F. Balfourier; V. Allard; M. Rousset (Theoretical and Applied Genetics, 2012)

Geochronological and geochemical characterization of magmatic-hydrothermal events within the Southern Variscan external domain (Cévennes area, France) - A. Chauvet; N. Volland-Tuduri; C. Lerouge; V. Bouchot; P. Monié; X. Charonnat; M. Faure (International Journal of Earth Sciences, 2012)

Field observations from the Aquila, Italy earthquake of April 6, 2009 - T. Rossetto; N. Peiris; J. E. Alarcon; E. So; S. Sargeant; M. Free; V. Sword-Daniels; D. Del Re; C. Libberton; E. Verrucci; P. Sammonds; J. Faure Walker (Bulletin of Earthquake Engineering, 2011)

Proteomic analysis reveals differentially expressed proteins in the rat frontal cortex after methamphetamine treatment - J. J. Faure; S. M. Hattingh; D. J. Stein; W. M. Daniels (Metabolic Brain Disease, 2009)

Land use monitoring by remote sensing in tropical forest areas in support of the Kyoto Protocol: the case of French Guiana - N. Stach; A. Salvado; M. Petit; J. F. Faure; L. Durieux; C. Corbane; P. Joubert; D. Lasselin; M. Deshayes (International Journal of Remote Sensing, 2009)

Comparative phylogeography among hydrothermal vent species along the East Pacific Rise reveals vicariant processes and population expansion in the South - S. PLOUVIEZ; T. M. SHANK; B. FAURE; C. DAGUIN‐THIEBAUT; F. VIARD; F. H. LALLIER; D. JOLLIVET (Molecular Ecology, 2009)
The use of sequence polymorphism from individual mitochondrial genes to infer past demography has recently proved controversial because of the recurrence of selective sweeps acting over genes and the need for unlinked multilocus data sets. However, comparative analyses using several species for one gene and/or multiple genes for one species can serve as a test for potential selective effects and clarify our understanding of historical demographic effects. This study compares nucleotide polymorphisms in mitochondrial cytochrome oxidase I across seven deep‐sea hydrothermal vent species that live along the volcanically active East Pacific Rise. Approximate Bayesian Computation (ABC) method, developed to trace shared vicariant events across species pairs, indicates the occurrence of two across species divergence times, and suggests that the present geographical patterns of genetic differentiation may be explained by two periods of significant population isolation. The oldest period dates back 11.6 Ma and is associated with the vent limpet Lepetodrilus elevatus , while the most recent period of isolation is 1.3 Ma, which apparently affected all species examined and coincides with a transition zone across the equator. Moreover, significant negative Tajima’s D and star‐like networks were observed for all southern lineages, suggesting that these lineages experienced a concomitant demographic and geographical expansion about 100 000–300 000 generations ago. This expansion may have initiated from a wave of range expansions during the secondary colonization of new sites along the Southern East Pacific Rise (founder effects below the equator) or recurrent bottleneck events because of the increase of eruptive phases associated with the higher spreading rates of the ridge in this region.

Incidence of kyphosis deformities in natural population of Atherina lagunae (Trabelsi et al. 2002) from the Tunis North Lake, Tunisia - N. Ayed; E. Faure; J.-P. Quignard; F. Maamouri; M. Trabelsi (Marine Biology, 2008)

Early maternal separation alters the response to traumatization: resulting in increased levels of hippocampal neurotrophic factors - Jacqueline Faure; Joachim D. K. Uys; Lelanie Marais; Dan J. Stein; Willie M. U. Daniels (Metabolic Brain Disease, 2007)

Structural, AMS and geochronological study of a laccolith emplaced during Late Variscan orogenic extension: the Rocles pluton (SE French Massif Central) - E. Be Mezeme; M. Faure; Y. Chen; A. Cocherie; J-Y. Talbot (International Journal of Earth Sciences, 2007)

Root-knot nematode (Meloidogyne spp.) Me resistance genes in pepper (Capsicum annuum L.) are clustered on the P9 chromosome - C. Djian-Caporalino; A. Fazari; M. J. Arguel; T. Vernie; C. VandeCasteele; I. Faure; G. Brunoud; L. Pijarowski; A. Palloix; V. Lefebvre; P. Abad (Theoretical and Applied Genetics, 2007)

Early maternal separation followed by later stressors leads to dysregulation of the HPA-axis and increases in hippocampal NGF and NT-3 levels in a rat model - Jacqueline Faure; Joachim D. K. Uys; Lelanie Marais; Dan J. Stein; Willie M. U. Daniels (Metabolic Brain Disease, 2006)

Phylogeography and population genetics of the maize stalk borer Busseola fusca (Lepidoptera, Noctuidae) in sub‐Saharan Africa - M. SEZONLIN; S. DUPAS; B. LE RÜ; P. LE GALL; P. MOYAL; P.‐A. CALATAYUD; I. GIFFARD; N. FAURE; J.‐F. SILVAIN (Molecular Ecology, 2006)
The population genetics and phylogeography of African phytophagous insects have received little attention. Some, such as the maize stalk borer Busseola fusca , display significant geographic differences in ecological preferences that may be congruent with patterns of molecular variation. To test this, we collected 307 individuals of this species from maize and cultivated sorghum at 52 localities in West, Central and East Africa during the growing season. For all collected individuals, we sequenced a fragment of the mitochondrial cytochrome b . We tested hypotheses concerning the history and demographic structure of this species. Phylogenetic analyses and nested clade phylogeographic analyses (NCPA) separated the populations into three mitochondrial clades, one from West Africa, and two — Kenya I and Kenya II — from East and Central Africa. The similar nucleotide divergence between clades and nucleotide diversity within clades suggest that they became isolated at about the same time in three different refuges in sub‐Saharan Africa and have similar demographic histories. The results of mismatch distribution analyses were consistent with the demographic expansion of these clades. Analysis of molecular variance ( amova ) indicated a high level of geographic differentiation at different hierarchical levels. NCPA suggested that the observed distribution of haplotypes at several hierarchical levels within the three major clades is best accounted for by restricted gene flow with isolation by distance. The domestication of sorghum and the introduction of maize in Africa had no visible effect on the geographic patterns observed in the B . fusca mitochondrial genome.

Parallels in the evolution of the two largest New and Old World seed‐beetle genera (Coleoptera, Bruchidae) - G. J. KERGOAT; N. ALVAREZ; M. HOSSAERT‐MCKEY; N. FAURE; J.‐F. SILVAIN (Molecular Ecology, 2005)
This study provides the first phylogenetic analysis of a large sample of the two largest genera of seed‐beetles, Acanthoscelides Schilsky and Bruchidius Schilsky, which mostly feed on legumes (Fabaceae). The goal of this study was to investigate evolutionary patterns in relation to biogeography and host‐plant associations. We used three mitochondrial molecular markers and parsimony and Bayesian inference methods to reconstruct the phylogeny of 76 species. In addition, we critically reviewed host‐plant records in the literature for these two bruchid genera. Our results demonstrated the existence of two major clades, one New World and one largely Old World, which generally correspond to the two genera. Yet, current classification of several species is erroneous, so that both genera as currently defined are paraphyletic. We highlighted a strong trend toward specialization (with high taxonomic conservatism in host‐plant use) exhibited by the two studied genera. However, we showed the existence of several host shifts during the evolution of this group of bruchids. Our phylogenetic hypotheses and our evaluation of host‐plant associations both suggest that the two genera have undergone parallel evolution, as they have independently colonized similar host plants in their respective areas of distribution. Our estimation of divergence times indicated a more ancient origin for bruchids than that suggested by the fossil records. Interestingly, the suggested timing of diversification is consistent with the hypothesis of a radiation that could have occurred contemporaneously with the diversification of their legume hosts.

Identification of type I resistance to Fusarium head blight controlled by a major gene located on chromosome 4A of Triticum macha - A. Steed; E. Chandler; M. Thomsett; N. Gosman; S. Faure; P. Nicholson (Theoretical and Applied Genetics, 2005)

Epidemiology of Candidaemia in Europe: Results of 28-Month European Confederation of Medical Mycology (ECMM) Hospital-Based Surveillance Study - A. M. Tortorano; J. Peman; H. Bernhardt; L. Klingspor; C. C. Kibbler; O. Faure; E. Biraghi; E. Canton; K. Zimmermann; S. Seaton; R. Grillot (European Journal of Clinical Microbiology & Infectious Diseases, 2004)

Screening of segregating cocoa genotypes for resistance to vascular-streak dieback under natural conditions in Papua New Guinea - Y. Efron; J. Marfu; M. Faure; P. Epaina (Australasian Plant Pathology, 2002)

Telescoped porphyry Cu-Mo-Au mineralisation, advanced argillic alteration and quartz-sulphide-gold-anhydrite veins in the Thames District, New Zealand - R. Brathwaite; M. Simpson; K. Faure; D. Skinner (Mineralium Deposita, 2001)

Hercynian polyphase tectonics in the northeast French Massif Central: the closure of the Brévenne Devonian-Dinantian rift - C. Leloix; M. Faure; J.-L. Feybesse (International Journal of Earth Sciences, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Plant regeneration and transient GUS expression in a range of lavandin (Lavandula × intermedia Emeric ex Loiseleur) cultivars - S. Dronne; M. Colson; S. Moja; O. Faure (Plant Cell, Tissue and Organ Culture (PCTOC), 1998)

Cadmium Accumulation and Metallothionein Biosynthesis in Cyprinus carpio Tissues - C. De Conto Cinier; M. Petit-Ramel; R. Faure; M. Bortolato (Bulletin of Environmental Contamination and Toxicology, 1998)

Pharmacokinetics of intravenous methylprednisolone and oral prednisone in paediatric patients with inflammatory bowel disease during the acute phase and in remission - C. Faure; J. André; C. Pelatan; A. Munck; M. Giraud; J. P. Cèzard; E. Jacqz-Aigrain (European Journal of Clinical Pharmacology, 1998)

Holocene sea level changes and reef development in the southwestern Indian Ocean - G. F. Camoin; M. Colonna; L. F. Montaggioni; J. Casanova; G. Faure; B. A. Thomassin (Coral Reefs, 1997)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Relationships between coral reef substrata and fish - P. Chabanet; H. Ralambondrainy; M. Amanieu; G. Faure; R. Galzin (Coral Reefs, 1997)